Outboard Onset of Ross Orogen Magmatism and Subsequent Igneous and Metamorphic Cooling Linked to Slab Rollback during Late-Stage Gondwana Assembly - Timothy Paulsen; John Encarnación; Anne Grunow; Jeffrey Benowitz; Paul Layer; Chad Deering; Jakub Sliwinski (Geosciences, 2023)
Changes in magmatism and sedimentation along the late Neoproterozoic-early Paleozoic Ross orogenic belt in Antarctica have been linked to the cessation of convergence along the Mozambique belt during the assembly of East-West Gondwana. However, these interpretations are non-unique and are based, in part, on limited thermochronological data sets spread out along large sectors of the East Antarctic margin. We report new 40Ar/39Ar hornblende, muscovite, and biotite age data for plutonic (n = 13) and metasedimentary (n = 3) samples from the Shackleton–Liv Glacier sector of the Queen Maud Mountains in Antarctica. Cumulative 40Ar/39Ar age data show polymodal age peaks (510 Ma, 491 Ma, 475 Ma) that lag peaks in U-Pb igneous crystallization ages, suggesting igneous and metamorphic cooling following magmatism within the region. The 40Ar/39Ar ages are similar to ages in other sectors of the Ross orogen, but younger than detrital mineral 40Ar/39Ar cooling ages indicative of older magmatism and cooling of unexposed inboard areas along the margin. Detrital zircon trace element abundances suggest that the widespread onset of magmatism in outboard localities of the orogen correlates with a ~560–530 Ma decrease in crustal thickness. The timing of crustal thinning recorded by zircon in magmas overlaps with other evidence for the timing of crustal extension, suggesting that the regional onset of magmatism with subsequent igneous and metamorphic cooling probably reflects slab rollback that coincided with possible global plate motion changes induced during the final assembly of Gondwana.